Enhancing Security and Privacy of CCTV Data in Smart Cities through Digital Watermarks and Smart Contracts (Sebha University Conference Proceedings, 2025)
Video surveillance plays a crucial role in smart cities, enhancing security, safety, monitoring, and analysis across various applications. These systems often collect data that includes sensitive information related to privacy, crime, and national security. Ensuring the authenticity and integrity of video footage is essential to confirm that the data comes from a legitimate and authorized source, which is critical for both security and legal purposes. An unverified video source in a surveillance system can present significant risks, as altered or manipulated footage may mislead investigations and result in wrongful accusations or convictions. Improving traceability within video surveillance systems is therefore vital for effectively tracking, verifying, and managing video data. This paper proposes a method that combines digital watermarking to prevent tampering or frame replacement with smart contracts to provide source verification and traceability for surveillance data.